Content Creators in the Digital Era (5.0): Phenomena and Its Benefits - Uci Widya Astuti; Hikmah Hikmah; Guntur Suryo Putro; Arfiany; Nurhidayanti (IECON: International Economics and Business Conference, 2023)
This study aims to determine the content creator phenomenon in the era of globalization 5.0 and see what benefits it brings to companies. In this study, several informants were used who were considered very capable in providinginformation about creator content in today's digital era. The research method used is qualitative with the phenomenological approach of Alferd Schutz. The way to collect data in this research is by way of interviews, observationand literature review. The results of this study are to describe the phenomenon of creator content in the digital 5.0 era which shows that in the current digital era there have been many new changes. These changes open up opportunities for users to try new things and be open to the outside world. Many people today are starting to open up to new things and slowly adjust to the development of existing technology. The digital era, provides convenience and human facilities to carry out activities or mobilize in everyday life. Being a content creator can be done as a side job. Being a content creatormeans being able to work anywhere and anytime. Content creators have the freedom to create a persona or discuss any topic they want. Content creators can provide new information and or facts to the public. The benefit of content creatorsfor companies is to brand the company so that it can be recognized by the wider community. Therefore the use of digitalmedia in the 5.0 era is expected to be able to make good use of it and be able to produce through digital media.